Inbound halal logistics practices: a case of local mosques - Kamarulzaman, Nitty Hirawaty; Ahmad Tarmizi, Hazwani (HH Publisher, 2020)
The involvement of multiple supply chain players across the mosque food supply chain has led to halal problems, particularly cross-contamination between halal and haram of raw materials during inbound logistics. This study aims to determine factors that influence inbound halal logistics practices among local mosques. Stratified random sampling was used to select the target local mosques in Peninsular Malaysia. Responses from the mosque management committees were obtained through self-administrated questionnaires. Descriptive analysis, mean score analysis, factor analysis, and logistic regression analysis were performed to analyze the data and to determine the factors that mostly influenced inbound halal logistics practices among local mosques. The findings showed that knowledge, dedicated facilities, religious responsibility, management support, financial resources, course and training, and trust were the factors that influenced inbound halal logistics practices among local mosques. This study recommends continuous course and training on halal logistics should be held by the local mosques and specific guidelines on halal logistics should be made available to ensure inbound halal logistics practices could be performed well by the local mosques.